2022
DOI: 10.3389/fgene.2022.861096
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism Analysis of LINC00665 and Its Peptides CIP2A-BP in Hepatocellular Carcinoma

Abstract: Background: More and more studies show that long non-coding RNAs (lncRNAs) have miniature open reading frames that can be translated into short peptides. Here, we identify the long non-coding gene LINC00665 and its short peptides (CIP2A-BP) in hepatocellular carcinoma (HCC) and explore how they contribute to HCC progression.Materials and methods: First, GSE101728 data were acquired through the Gene Expression Omnibus for identification of differentially expressed genes (DEGs), and gene set enrichment analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…Third, micropeptides affect various tumor phenotypes, including cell proliferation, metastasis, and invasion. The subtle and specific mechanisms remain to be further explored and can be expanded to other related fields by comprehensively elaborating the signaling pathways 48,49 . Furthermore, accurately analyzing the intracellular localization, translation level, functional mechanisms, and special structures of micropeptides is conducive to developing micropeptides as biological diagnostic and prognostic indicators and potential therapeutic tumor targets.…”
Section: Methods and Technologies For Predicting And Characterizing S...mentioning
confidence: 99%
“…Third, micropeptides affect various tumor phenotypes, including cell proliferation, metastasis, and invasion. The subtle and specific mechanisms remain to be further explored and can be expanded to other related fields by comprehensively elaborating the signaling pathways 48,49 . Furthermore, accurately analyzing the intracellular localization, translation level, functional mechanisms, and special structures of micropeptides is conducive to developing micropeptides as biological diagnostic and prognostic indicators and potential therapeutic tumor targets.…”
Section: Methods and Technologies For Predicting And Characterizing S...mentioning
confidence: 99%
“…A specificity protein 1 (SP1)-induced long non-coding RNA, DPPA2 upstream binding RNA (DUBR), upregulates CIP2A expression through E2F1-mediated transcription regulation, which also plays a role in upregulating CIP2A at the mRNA level by binding miR-520d-5p as a competing endogenous RNA (Liu et al, 2022). The knockdown of LINC00665 can also significantly decrease the cell proliferation, migration, and invasion of HCC, while overexpression of the short peptides of LINC00665 (CIP2A-BP) can markedly increase cell proliferation, invasion, and migration (Li et al, 2022).…”
Section: Non-coding Rnamentioning
confidence: 99%
“…Moreover, it can regulate the viability, apoptotic pathways, and autophagy of these cells through modulation of miR-186-5p/MAP4K3 [ 21 ] and Double-Stranded RNA–Activated Protein Kinase/NF-κB [ 22 ] axes. Another study in hepatocellular carcinoma cells has shown that LINC00665 silencing could decrease proliferation, migration, and invasion, whereas up-regulation the CIP2A-BP micropeptide enhances these features [ 36 ].…”
Section: Cell Line Studiesmentioning
confidence: 99%
“…Moreover, up-regulation of LINC00665 has been associated with further development of the tumors, which has been closely correlated with clinical diagnosis. Accuracy of LINC00665 levels in prediction of overall survival has also been verified by ROC curve analyses [ 36 ].…”
Section: Studies In Clinical Samplesmentioning
confidence: 99%